PENGEMBANGAN WISATA KOTA PADANG SEBAGAI DESTINASI WISATA KOTA DI SUMATERA BARAT - Putri, Rozana Eka (Jurnal Spasial, 2016)
Padang is the capital city of West Sumatra lies on the western shore of the island of Sumatra is an area of great tourist destination to visit due to have a natural potential that is different from other areas and also has the potential to represent the culture of Minangkabau culture such as museums Aditiawarman, bridges and other sitinurbaya. Tourism Development of the City field will be an interesting trend in the future by many rational reasons, it can increase revenue. Regional or PAD Asi income can be increased through tax Hotel, Restaurant Tax and Economic Activity Increases in urban areas .Some of the obstacles that could hinder the development of tourism in the city of the plain, namely: 1) the ineffectiveness of the regulation in order to control the effectiveness of development and tourism development. With regard to the regional autonomy in the implementation of development demanded the regulation of executive functioning optimally on the development of culture and tourism 2) Lack of tourism facilities and infrastructure. Their facilities and infrastructure in the region repfesentatif travel site is a certain appeal. 3) The lack of coordination and cohesion among stakeholders as well as program-related sectors. The role and involvement of stakeholders in the development of culture and tourism is still lacking, particularly in the development of an area. 4) Lack of quality and quantity of tourism human resources professional and highly capable. Tourism players are very less in number and quality is not in accordance with the existing resources in the office or in the field. 5) Not optimal marketing and promotional programs that provide positive contribution to revenue (PAD) Implementation of tourism promotion uncultivated areas is not optimal, elements of tourism promotion is expected to be the main tool to destination to the city of Padang. 6) There optimal development of management and conservation of objects and tourist Drag and local cultures. The need for the development and preservation of regional destinations, such as for regional cultural tourism and history as a leading tourism destination and objects. 7) Not optimal network is a community-basedpartnerships. Required professional handling of stakeholders involvement of stakeholders in tourism development efforts are directed